EFEKTIVITAS POLA KEMITRAAN “P4S ARTHA TANI” DI KECAMATAN SUSUKAN KABUPATEN BANJARNEGARA - Bayu Nurwansyah; Yusuf Enril Fathurrohman; Pujiati Utami (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2023)
The objectives of this study were: 1) To identify the socio-economic factors that contribute to participation in the partnership model and 2) To assess the effectiveness of the ongoing partnership model. The research method used was qualitative descriptive using a Likert scale. The sampling technique used was purposive sampling based on specific criteria, resulting in the selecting of 24 core members of the Farmers Group. The social factors involved included a good relationship between the Farmers Group and P4S Artha Tani, while the economic factor was the participation of the Farmers Group in the training and mentoring provided. The overall effectiveness of the partnership model, as measured by indicators of program clarity, facilitator quality, and business development, was rated as Highly Effective. Thus, the partnership between P4S Artha Tani and the Farmers Group of GAPOKTAN Taruna Tani in Susukan District, Banjarnegara Regency, has been running well in achieving the desired goals of both partnering parties.